Nocardia nova as the Causative Agent in Spondylodiscitis and Psoas Abscess - Hamdad, Farida (American Society for Microbiology, 2007)
We describe here the first case of Nocardia nova spondylodiscitis accompanied by a psoas abscess due to spreading from pulmonary nocardiosis. Nocardia was cultured from all affected sites. After 1 year of an appropriate antimicrobial therapy and a surgical drainage of the abscess that was required, the patient's clinical condition had improved.